Simulation of particle motion in still a rough surface and its testing for example inclined plane - Nesvidomin, A. (Energy and Automation, 2017)
Annotation. A analytical, algorithmic and software simulation of a particle on any stationary rough surface as a function of time, the position of the particles on the surface and the direction of its movement. Algorithm worked out by the example of the inclined plane.Key words: material point, trihedron, inclined plane, rough surface modelingThe method of computer modeling of a particle along rough surface which is based on: 1) the inner surface parameterization: 2) supporting trihedron curves on the surface; 3) independent parameters forming curves on the surface, which is the time the particle position and direction of its movement on the surface.ment. Algorithm worked out by the example of the inclined plane. Key words: material point, trihedron, inclined plane, rough surface modeling